FUTURE TEACHERS OF FINE ARTS IN THE FINE ARTS TO ARTISTIC ANALYSIS OF HIS WORKS IN THE LANDSCAPE GENRE PREPARATION ISSUES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the future visual arts will bring teachers to the landscape in the visual arts topical issues of preparing works of the genre for the activities of artistic pseudonym lit. The cultivation of independent creative abilities of students in the credit-module system, in which on the independent solution of existing problems related to the professions they occupy requires the formation of skills and abilities. In particular, the upcoming specialization in the preparation of teachers of Fine Arts, along with all disciplines education of subjects at the required level also plays an important role.